2020
DOI: 10.1111/and.13884
|View full text |Cite
|
Sign up to set email alerts
|

Sperm source does not affect the ICSI outcome of patients with severely compromised spermatogenesis

Abstract: Patients with spermatogenic dysfunction may display sperm parameters ranging from extremely severe oligozoospermia (sperm count lower than 2 million/ml) to azoospermia. It has been proposed that, since these patients may have increased sperm DNA damage that could affect their ICSI outcome, the use of surgically retrieved testicular spermatozoa should be preferred to improve their chance of fathering their biological offspring. However, studies in this field have yielded conflicting results. The present study p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…In this study, embryonic cells were cultured in vitro until the 3rd or 5th day for transfer, and the number of transplanted embryos was roughly the same in all four groups. The study (Caroppo et al, 2020) compared the ICSI results of testicular sperm and ejaculated sperm patients without significant differences in clinical outcomes, which was consistent with our research results, and proposed to oppose the use of testicular sperm in patients with extremely severe spermatogenesis disorders who had available sperm in their semen. It (Morin et al, 2020) was also suggested that there was no difference in the live birth rate between testicular‐derived and epididymal‐derived blastocysts.…”
Section: Discussionsupporting
confidence: 88%
“…In this study, embryonic cells were cultured in vitro until the 3rd or 5th day for transfer, and the number of transplanted embryos was roughly the same in all four groups. The study (Caroppo et al, 2020) compared the ICSI results of testicular sperm and ejaculated sperm patients without significant differences in clinical outcomes, which was consistent with our research results, and proposed to oppose the use of testicular sperm in patients with extremely severe spermatogenesis disorders who had available sperm in their semen. It (Morin et al, 2020) was also suggested that there was no difference in the live birth rate between testicular‐derived and epididymal‐derived blastocysts.…”
Section: Discussionsupporting
confidence: 88%
“…Spermatogenic dysfunction was characterized by the impairment of intratesticular spermatogenesis, and NOA is the most severe condition of it 103 . NOA was clinically diagnosed with no sperm in ejaculates along with evidence reflecting/causing the impairment of testicular spermatogenesis (e.g., elevated FSH or history of chemotherapy) 104 .…”
Section: Resultsmentioning
confidence: 99%
“…This result is similar in previous reports of the association between testicular volume and hormonal level with testicular histopathology. 6,18,19 who already For each unit increase in FSH concentration, the odd of a more severe histopathological pattern increased by 7.1% (95%CI: 1.01-1.12).…”
Section: Probability Of Histopathological Pattern According To Fsh Levelmentioning
confidence: 96%